Exploring the combined diagnostic role of serum MBL in association with renal resistive index and renal shear wave elastography in diabetic kidney disease patients - Enas Ahmed Osman; Khaled Mabrouk; Ahmed Abdelsamie Mahmoud; Medhat Madbouly; Mohamed Moharam Mohamed Hussin; Osama Mosbah; Nevine Sherif; Mohammed Ghanem Gaber; Farida M. Khanany (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background One of the most prevalent non-communicable diseases in the world today is diabetes. Diabetic kidney disease (DKD) is the predominant etiology of chronic kidney disease (CKD) and a major side effect of diabetes. Diagnosis of DKD is challenging and imprecise; thus, new diagnostic modalities are necessary to address this problem. The aim of the present study is to assess the role of the combined diagnostic performance of serum levels of MBL and imaging techniques, Doppler ultrasonographic renal resistive index (RRI) and shear wave elastography as a diagnostic tool for diabetic nephropathy. This case–control study included 450 type 2 diabetes mellitus (T2DM) patients, 225 without nephropathy and 225 diagnosed with diabetic nephropathy. We evaluated serum mannose-binding lectin (MBL) by enzyme-linked immunosorbent assay (ELISA) as a marker of diabetes-related inflammation, Doppler ultrasonographic renal resistive index (RRI) as a tool for assessment of blood flow in the kidney and shear wave elastography (SWE) as an imaging technique for detection of kidney fibrosis. Result The average serum MBL levels, mean RI and SWE of both kidneys were significantly higher in DKD patients compared to T2DM patients without nephropathy. The integration of the aforementioned methodologies significantly enhanced diagnostic performance, achieving a sensitivity of 96.89% and a specificity of 95.11%. Conclusion Combined serum levels of MBL and imaging techniques, Doppler ultrasonographic renal RI and shear wave elastography are promising diagnostic tools of diabetic nephropathy.